2012
DOI: 10.1155/2012/714732
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis in Juvenile Idiopathic Arthritis

Abstract: Atherosclerosis is a chronic inflammatory disease of the arteries. Clinical consequences of the atherosclerotic process occur in the adult population, however atherosclerotic process begins in childhood. The classic risk factors for atherosclerosis include obesity, dyslipidaemia, age, gender or family history. In recent years, attention has been drawn to the similarity between atherosclerotic inflammatory processes and inflammatory changes in the course of systemic connective tissue disease, in particular syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
(30 reference statements)
3
20
0
2
Order By: Relevance
“…The administration of IL-6 to mice susceptible to atherosclerosis and to mice resistant to atherosclerosis receiving a cholesterol-rich diet resulted in atherosclerotic lesions developing only in mice susceptible to atherosclerosis [ 37 ]. The increased levels of proinflammatory cytokines are observed in RA [ 38 ], similarly in children with JIA [ 39 ]. In studies on patients with RA, IL-6 played an especially vital role in the vascular endothelial activation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The administration of IL-6 to mice susceptible to atherosclerosis and to mice resistant to atherosclerosis receiving a cholesterol-rich diet resulted in atherosclerotic lesions developing only in mice susceptible to atherosclerosis [ 37 ]. The increased levels of proinflammatory cytokines are observed in RA [ 38 ], similarly in children with JIA [ 39 ]. In studies on patients with RA, IL-6 played an especially vital role in the vascular endothelial activation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, it has been shown that multiple rheumatic diseases including RA, scleroderma, ankylosing spondylitis, systemic lupus erythematosus and gout may be associated with hyperhomocysteinemia, which may, in turn, be associated with cardiovascular events (6)(7)(8)(9). In many studies that examined serum Hcy levels in rheumatic disease, serum Hcy levels were higher in the case group than the control group (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…There are very scarce published data on subclinical atherosclerosis in patients with JIA, reviewed in [10]. Recent studies showed increased IMT in JIA children or impaired endothelial function in these patients [11, 12].…”
Section: Introductionmentioning
confidence: 99%